2022
DOI: 10.1101/2022.02.15.480508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An umbrella review of randomized control trials on the effects of physical exercise on cognition

Abstract: Many meta-analytic reviews have examined the cognitive benefits of regular physical exercise across the lifespan, with a wide range of inclusion criteria and disparate analytic approaches. In fact, most global health organizations incorporate the purported cognitive benefits as part of their policies to promote regular physical exercise. We assess whether those claims are well supported by scientific evidence. We conducted a pre-registered (PROSPERO: CRD42020191357) umbrella review of meta-analyses limited to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 218 publications
1
6
0
Order By: Relevance
“…Although several studies have suggested a link between cognitive function and moderate‐to‐vigorous physical activity for various populations and ages, albeit with small‐to‐moderate treatment effects and heterogeneous study designs (Erickson et al., 2019; Oberlin et al., 2017), we did not find support for neither an association between cognitive performance and baseline physical activity level of different intensities nor association between response to cognitive training and activity level in the current study. This finding is in line with a recent meta‐analysis of randomized controlled studies on healthy populations, suggesting only small benefits of exercise on cognition and no benefit if correcting for publication biases (Ciria et al., 2023). The current findings underpin the complexity within this field of research and suggest that other factors might be stronger indicators of the performance and success of cognitive training, in chronic phase, than baseline activity level.…”
Section: Discussionsupporting
confidence: 89%
“…Although several studies have suggested a link between cognitive function and moderate‐to‐vigorous physical activity for various populations and ages, albeit with small‐to‐moderate treatment effects and heterogeneous study designs (Erickson et al., 2019; Oberlin et al., 2017), we did not find support for neither an association between cognitive performance and baseline physical activity level of different intensities nor association between response to cognitive training and activity level in the current study. This finding is in line with a recent meta‐analysis of randomized controlled studies on healthy populations, suggesting only small benefits of exercise on cognition and no benefit if correcting for publication biases (Ciria et al., 2023). The current findings underpin the complexity within this field of research and suggest that other factors might be stronger indicators of the performance and success of cognitive training, in chronic phase, than baseline activity level.…”
Section: Discussionsupporting
confidence: 89%
“…Relatedly, the negative effects of social isolation on cognitive health may accumulate over years or decades and therefore not be detectable until late life. This remains unknown, however, as much of the relevant animal and human studies have not considered lifespan changes in these associations (47,54). Moreover, the presence of indirect effects yet absence of total effects (as occurred in older men) might be a statistical phenomenon, resulting from greater statistical power to detect indirect effects compared with total or direct effects (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The measure of physical activity used in our study incorporates both frequency and intensity of activities, and therefore, it is important to acknowledge that both the frequency and the intensity of activities are important dimensions to consider when designing targeted interventions. The effects of physical activity on cognition have been studied extensively, with the results of randomized controlled trials showing a modest, positive impact of physical exercise training-typically aerobic-focused walking programs-on memory and EF (47). In addition to the more direct neurobiological effects on the brain (48), physical activity may promote cognition through the social and cognitive stimulation that often occurs during activity (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…This small sample size precludes high statistical power, which may explain the lack of relationship between CRF and executive performances. The use of a larger sample size is therefore essential and to achieve this, researchers need to standardize their experimental protocol to perform a multilaboratory study (Ciria et al, 2022). Another limitation was that we measured only two of the three core EFs.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, it appears that very few studies have examined the relationship between CRF and EFs in young adults. In addition, a recent umbrella review of randomized controlled trials on the effects of physical exercise on cognition suggests that the evidence might not be reliable and therefore no strong conclusions should be drawn based on existing evidence (Ciria et al, 2022).…”
Section: Introductionmentioning
confidence: 99%